Simulation of cyber threats for the Internet of Things - Belov, Alexander; Delembovsky, Maxim; Shklyar, Vitaliy (Transfer of innovative technologies, 2021)
The modern world is impossible to imagine without information technology. Such technologies are based on the use of computer equipment and means of communication. Both in the real world and in the virtual world, there are crimes called "cybercrimes". Thus, energy facilities, transport systems, financial and banking structures, military and law enforcement agencies, trade, medical and scientific institutions are potential victims of cybercrime, including cyberterrorism. Surveillance cameras, motion sensors, biochips, smart appliances - all these things simplify our daily lives and make our modern life more comfortable. As the number of devices connected to the network grows, so does the number of cyber threats. For example, the smart refrigerator became part of the botnet and began to spread spam, and the smart coffee machine was the cause of the attack on industrial networks with the subsequent infection of computers. The Internet of Things, which in turn is simple and difficult to implement, also has some problems with information security. Sometimes developers, intentionally or unintentionally, leave an undocumented channel, which not only collects information about the use of the device, but also allows you to penetrate into the personal space of the end user. In case of personal data leakage, the purpose of fraudsters is usually personal data: names, postal addresses, e-mail addresses, credit card details or account information. This allows you to order goods online under someone else's name and pay for them using someone else's debit card or debiting a certain account. For the same purpose, phishing can be used, which involves the use of fictitious websites, e-mails or text messages to access personal data.